Healthy Immigrant Families: Randomized Controlled Trial of a Family-Based Nutrition and Physical Activity Intervention. Issue 2 (February 2018) - Wieland, Mark L.; Hanza, Marcelo M. M.; Weis, Jennifer A.; Meiers, Sonja J.; Patten, Christi A.; Clark, Matthew M.; Sloan, Jeff A.; Novotny, Paul J.; Njeru, Jane W.; Abbenyi, Adeline; Levine, James A.; Goodson, Miriam; et al.
Purpose: To evaluate a healthy eating and physical activity intervention for immigrant families, derived through community-based participatory research. Design: The Healthy Immigrant Families study was a randomized controlled trial with delayed intervention control group, with families as the randomization unit. Setting: US Midwest city. Participants: Participants were recruited by community partners from Hispanic, Somali, and Sudanese immigrant communities. Intervention: Family health promoters from participating communities delivered 6 healthy eating modules, 4 physical activity modules, and 2 modules synthesizing information in 12 home visits (60-90 minutes) within the first 6 months. Up to 12 follow-up phone calls to each participant occurred within the second 6 months. Measures: Primary measures were dietary quality measured with weekday 24-hour recall and reported as Healthy Eating Index score (0-100) and physical activity measured with accelerometers (14 wear days) at baseline, 6, 12, and 24 months. Results: In total, 151 persons (81 adolescents and 70 adults; 44 families) were randomly assigned. At 12 months, significant improvement occurred in Healthy Eating Index scores for adults in the intervention group compared with controls (change, +8.6 vs −4.4; P < .01) and persisted at 24 months (+7.4 from baseline; P < .01). No differences were observed for adolescents and no significant differences occurred between groups for physical activity. Conclusion: This intervention produced sustained dietary quality improvement among adults but not among adolescents. Program outcomes are relevant to communities working to decrease cardiovascular risk among immigrant populations.